2012
DOI: 10.1086/663236
|View full text |Cite
|
Sign up to set email alerts
|

Segregation That No One Seeks

Abstract: This article examines a series of Schelling-like models of residential segregation, in which agents prefer to be in the minority. We demonstrate that as long as agents care about the characteristics of their wider community, they tend to end up in a segregated state. We then investigate the process that causes this and conclude that the result hinges on the similarity of informational states among agents of the same type. This is quite different from Schelling-like behavior and suggests (in his terms) that seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…Using a formal language forces the reasoner to explicate implicit assumptions, and makes the comparison of inferences from similar yet different assumptions easier. This is what many sociologists and economists following Schelling's idea have been doing (Bruch & Mare 2006Clark & Fossett 2008;Fossett 2006;Macy & van de Rijt 2006;Muldoon, Smith & Weisberg 2012). They have shown that segregation indeed arises due to the 'tipping point' phenomenon, where the first moves of even a few dissatisfied agents can create an incentive for others to move.…”
Section: Models As Extended Cognitionmentioning
confidence: 89%
See 1 more Smart Citation
“…Using a formal language forces the reasoner to explicate implicit assumptions, and makes the comparison of inferences from similar yet different assumptions easier. This is what many sociologists and economists following Schelling's idea have been doing (Bruch & Mare 2006Clark & Fossett 2008;Fossett 2006;Macy & van de Rijt 2006;Muldoon, Smith & Weisberg 2012). They have shown that segregation indeed arises due to the 'tipping point' phenomenon, where the first moves of even a few dissatisfied agents can create an incentive for others to move.…”
Section: Models As Extended Cognitionmentioning
confidence: 89%
“…This accusation is quite unfair, since checkerboard models have been studied for over forty years by a multitude of scholars in various disciplines and thus many of the consequent findings should not be read back to the original models. The segregation equilibrium seems to be a robust outcome in many of the modifications to the model's structural assumptions (Aydinonat 2007;Muldoon, Smith & Weisberg 2012). Most changes in the size of the neighborhood, individual preferences, or the availability of apartments do not change the segregated outcome.…”
mentioning
confidence: 99%
“…Indeed, it is questionable whether Schelling's result was altogether surprising for other modellers. For although the degree of segregation that emerges in this model is much higher than individuals' preferences for homogeneity, individuals are still assumed to prefer some degree of homogeneity in their respective neighbourhoods (Muldoon et al, 2012). Taken together, these observations make it doubtful that the necessity hypothesis that is allegedly contradicted by Schelling's model was widely endorsed at the time this model was published.…”
Section: Schelling's Checkerboard Modelmentioning
confidence: 93%
“…In fact, recent studies have shown that segregation may emerge even in cases where individuals strictly prefer to live in diverse communities and be surrounded by agents of a different type (see e.g. Muldoon et al, 2012).…”
Section: Schelling's Checkerboard Modelmentioning
confidence: 99%
“…We will call it the family of models thesis. It turns out that the segregation equilibrium seems to be a robust outcome in many of the modifications to the model's assumptions (Aydinonat 2007;Muldoon, Smith & Weisberg 2012).…”
Section: Family Of Models Thesismentioning
confidence: 99%